Dosimetric evaluation of Acuros XB dose calculation algorithm with measurements in predicting doses beyond different air gap thickness for smaller and larger field sizes - Rana, Suresh; Rogers, Kevin (Journal of medical physics, 2013)
In this study, dose prediction accuracy of Acuros XB (AXB) dose calculation algorithm beyond air gap thickness (range 2, 4, and 6 cm) in simple inhomogeneous phantoms was investigated. The evaluation of AXB was performed by comparing the doses calculated by AXB with the doses calculated by Anisotropic Analytical Algorithm (AAA) and the measured data for different field sizes (3 × 3, 5 × 5, and 10 × 10 cm 2 ) of a 6 MV photon beam. The dose computation was performed within Eclipse treatment planning system, and measurements were acquired with a cylindrical ionization chamber. Central axis depth dose comparisons were done in solid-water material region up to 5 cm distance from air/solid-water interface. The results of AXB had better agreement with measurements at all measured points than that of AAA. The discrepancies between AXB and measured data were seen from − 3.81% to + 0.9%, whereas the AAA differences with measurement from − 3.1% to − 10.9%. The combination of the smallest test field size and the largest air gap produced the highest range (1-5 cm distance from air/solid-water interface) in dose difference (AAA: −4.0% to − 10.6% and AXB: −3.8% to + 0.6%). The AAA computational time was about 8 times faster than that of AXB. In conclusion, AXB is more appropriate to use for dose predictions, especially when low-density heterogeneities are involved.